Renewable Energy Curtailment Storage in Molten Salt and Solid Particle Solar Thermal Power Plants: A Comparative Analysis in Spain - Sergio González-Barredo; Miguel Ángel Reyes-Belmonte (Applied Sciences)
Spain’s energy transition poses the dual challenge of managing renewable curtailment and enhancing the competitiveness of concentrated solar power (CSP) technologies. This study evaluates the suitability of replacing molten salts with solid particles for energy storage and, additionally, explores the storage of surplus electricity from grid in Carnot batteries. Four scenarios were analyzed using a Gemasolar-type plant model: each storage medium was studied with and without the integration of curtailed electricity. The solar field was modeled with SAM (System Advisor Model), while curtailment data from Red Eléctrica de España (2016–2021) quantified the available surplus. Results show that solid particles lead to 7.4% higher annual electricity production compared to molten salts, mainly due to improved power cycle efficiency. The integration of curtailment increased output further, with the solid particle Carnot battery scenario achieving the highest performance (up to 19.0% sun-to-electricity efficiency and 69.7% capacity factor). However, round-trip efficiency for curtailment storage was limited (~25–27%), and although solid particles showed lower LCOE (levelized cost of energy) than salts (192 vs. 211 USD/MWh), the Carnot battery increased costs. These findings suggest that while solid particles offer clear advantages, the economic viability of Carnot batteries remains constrained by current cost and operational limitations.